Sedimentology and volumetric reconstitution of recent mud and debris flows deposits in alluvial plain: a study in the Jacareí river basin (southern coast of Brazil) - Paz, Otacílio Lopes de Souza; Paula, Eduardo Vedor (Sociedade & Natureza, 2022)
Extreme mud and debris flows can bury alluvial plains. In current literature, there exists a significant knowledge gap regarding this process, since information about the sedimentological characteristics and estimates of the volumes of these deposits, are still scarce. Such knowledge is important for understanding the role of these events in the morphogenesis of the alluvial plains of the highland mountain margins. The study area located in the Jacareí River basin (coast of the State of Paraná, Brazil) was recently buried by mud slides in March 2011, therefore, our objective is to analyze the sedimentology and estimate the volume of instantaneous deposits formed by the aforementioned gravitational processes. The deposits were mapped based on a geospatial database. Afterwards, samples were collected for laboratory analysis. To estimate the volume, field samples were collected, measuring the thickness of the deposits, which were then interpolated in a GIS environment. Pelitic (9%), psephytic (4%) and psammitic (87%) deposits were identified. The psammitic deposits showed two distinct behaviors as a function of the flow and burial dynamics of the alluvial plain. The total volume of the deposit was estimated at 1,7 million tons of sediment. The results demonstrate the magnitude of the 2011 event, since in a period of less than 24 hours the Jacareí river basin moved more than 8.5 times the annual production of sediments from the hydrographic units that drain into the Estuarine Complex of Paranaguá.